Ferroptosis: a new mechanism of traditional Chinese medicine for treating hematologic malignancies - Gou, Xinyue; Tang, Xudong; Liu, Chi; Chen, Zhuo (Frontiers in Oncology, 2024)
Ferroptosis is a recently identified form of cell death characterized by lipid peroxidation and elevated iron levels. It is closely associated with hematologic malignancies, including leukemia, multiple myeloma (MM), and myelodysplastic syndromes (MDS). Research indicates that ferroptosis could represent a novel therapeutic target for these hematologic malignancies. Furthermore, traditional Chinese medicine (TCM) has been shown to modulate hematologic malignancies through the ferroptosis pathway. This paper aims to elucidate the mechanisms underlying ferroptosis and summarize the current research advancements regarding ferroptosis in hematologic malignancies, as well as the role of traditional Chinese medicine in the prevention and treatment of ferroptosis, with the goal of enhancing treatment efficacy.